Temsirolimus Inhibits Proliferation and Migration in Retinal Pigment Epithelial and Endothelial Cells via mTOR Inhibition and Decreases VEGF and PDGF Expression - Liegl, Raffael; Koenig, Susanna; Siedlecki, Jakob; Haritoglou, Christos; Kampik, Anselm; Kernt, Marcus (PLOS ONE, 2014)
Due to their high prevalence, retinal vascular diseases including age related macular degeneration (AMD), retinal vein occlusions (RVO), diabetic retinopathy (DR) and diabetic macular edema have been major therapeutic targets over the last years. The pathogenesis of these diseases is complex and yet not fully understood. However, increased proliferation, migration and angiogenesis are characteristic cellular features in almost every retinal vascular disease. The introduction of vascular endothelial growth factor (VEGF) binding intravitreal treatment strategies has led to great advances in the therapy of these diseases. While the predominant part of affected patients benefits from the specific binding of VEGF by administering an anti-VEGF antibody into the vitreous cavity, a small number of non-responders exist and alternative or additional therapeutic strategies should therefore be evaluated. The mammalian target of rapamycin (mTOR) is a central signaling pathway that eventually triggers up-regulation of cellular proliferation, migration and survival and has been identified to play a key role in angiogenesis. In the present study we were able to show that both retinal pigment epithelial (RPE) cells as wells as human umbilical vein endothelial cells (HUVEC) are inhibited in proliferating and migrating after treatment with temsirolimus in non-toxic concentrations. Previous studies suggest that the production of VEGF, platelet derived growth factor (PDGF) and other important cytokines is not only triggered by hypoxia but also by mTOR itself. Our results indicate that temsirolimus decreases VEGF and PDGF expression on RNA and protein levels significantly. We therefore believe that the mTOR inhibitor temsirolimus might be a promising drug in the future and it seems worthwhile to evaluate complementary therapeutic effects with anti-VEGF drugs for patients not profiting from mono anti-VEGF therapy alone.